2021
DOI: 10.1016/j.foodchem.2020.128399
|View full text |Cite
|
Sign up to set email alerts
|

Whole, concentrated and reconstituted grape juice: Impact of processes on phenolic composition, “foxy” aromas, organic acids, sugars and antioxidant capacity

Abstract: The concentration and reconstitution processes of grape juices can result in losing compounds associated with beverage quality. In this context, three tanks containing 50,000 L of grape juice were individually concentrated up to 68 °Brix using a triple vacuum concentrator. The concentrated juice was reconstituted up to the original °Brix of the whole juice (18.4). Phenolic compounds, sugars and organic acids were quantified by high-performance-liquid-chromatography. "Foxy" aromatic compounds were also quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…It is noteworthy that the grape juice by itself was able to partially correct some of the genetic parameters (TNF-α, NOX2, HMOX1, and Nrf2). This is in agreement with previous studies on the antioxidant properties of grape products [ 54 ]. This antioxidant capacity has also been reported for other juices.…”
Section: Discussionsupporting
confidence: 94%
“…It is noteworthy that the grape juice by itself was able to partially correct some of the genetic parameters (TNF-α, NOX2, HMOX1, and Nrf2). This is in agreement with previous studies on the antioxidant properties of grape products [ 54 ]. This antioxidant capacity has also been reported for other juices.…”
Section: Discussionsupporting
confidence: 94%
“…Concentrated grape juice is a product obtained by physical methods for removing water and increasing the content of soluble solids present in the respective total juice by at least 50%. By diluting the concentration or dried juice to the initial concentration based on °Brix as reconstitution parameter, reconstituted grape juice is obtained (Dutra et al., 2021 ). Grape juices consist of water (81%–86%) and a high concentration of sugars (glucose and fructose), with high acidity owing to the existence of organic acids that balance the sweet and sour tastes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the experimental results indicated that the TAC and TPC of grape juice showed a positive correlation when the DPPH free radical scavenging method was used to measure the AOX activities (Dani et al ., 2007). Other studies have shown that AOX activities are related to the levels of anthocyanins and phenolic compounds, since an increase in AOX activity was observed in conjunction with increased phenolic content (Dutra et al ., 2021). On the other hand, the viable cell count in the FRGGJ also had a positive influence on AOX activities, as when the cell viability reached 10 6 –10 10 CFU mL −1 , the AOX activities of the mixed groups were higher than those of the single groups (Deeplina & Goyal, 2015).…”
Section: Resultsmentioning
confidence: 99%